ARRANJO E POPULAÇÕES DE PLANTAS E SUA INFLUÊNCIA EM CARACTERÍSTICAS AGRONÔMICAS E NA PRODUTIVIDADE DE TRIGO E CEVADA - Senger, Marina (2013)
The arrangement of plants spaced paired is one of the management practices being used in some cultures and has resulted in increased yield. Aiming to evaluate the arrangements and plant density on agronomic characteristics, yield components and yield of two cultivars of wheat and barley, there were four experiments, differing in culture and farming in the city of PontaGrossa, PR, 2012. The experimental design used in was randomized blocks in a 2x4 factorial design with four replications. The treatments consisted of two plant arrangements (single spaced and paired) and four plant densities (45, 60, 75 and90plantsm-1). Treatments were applied in two wheat cultivars (BRS-Tangará and Marfim) and two barley (BRSCauêandMN-743). Increasing plant density reduced the number of tillers, stem diameter and number of spikelets per spikein wheat and barley, promoted height increaseonly inBRSCauêand lowerthousand grain weightin cultivarsBRS-Tangará e Marfim. In bothwheat cultivarsspacingpairedpromotedfewerspikeper square meter, higherthousand grain weightandlower yield. In the twobarley cultivarsin the spacing paired occurred fewer spikes persquare meter.On BRS-Cauê pacingpairedincreasedyieldandMN-743 pairedspacinghigher yieldsin the density of90plantsper meter.